Fenomen svjatosti v formirovanii religioznogo soznanija: religiozno-fenomenologičeskij diskurs - Kamalova, F. (Chabaršy. Dintanu serijasy, 2022)
The article explores the phenomenon of holiness, which is of particular importance in the formation of religious consciousness. The research work analyzes the concept of holiness using historical-social, comparative-hermeneutical, religious-phenomenological approaches. As a result of the analysis, the theoretical and methodological foundations of the concept of holiness are proposed. In addition, a description of its scientific and practical significance in religious studies, theology, and religion in general is given. Also, from an ontological point of view, the sacred is considered as a high level of reality, separated from everyday life, from an epistemological point of view, true knowledge is beyond understanding, from a phenomenological point of view, the wonderful world, from an axiological point of view, is considered as an absolute, imperative phenomenon. Further, the role of the phenomenon of holiness in religious consciousness is emphasized. This is due to the fact that the content and specificity of religion as a sphere of spiritual life is determined by religious consciousness, and it is this consciousness that can relatively distinguish religion from other ways of practical and spiritual exploration of the world. Religious consciousness has a number of features: visualization caused by feeling, images created by the imagination, symbolism, strong emotional richness. Such features can also be described by the phenomenon of holiness. In addition, the concept of holiness, which is of paramount importance in the development of religious consciousness, arises in connection with mystery and genuine sensation. The value of the study is that the phenomenology of religion considers the concept of holiness in the context of scientific objectivity and shows that holiness determines the main forms found in religion in general, cult, religious understanding and religious consciousness.